MiT/TFE factors control ER‐phagy via transcriptional regulation of FAM134B. (27th July 2020) - Cinque, Laura; De Leonibus, Chiara; Iavazzo, Maria; Krahmer, Natalie; Intartaglia, Daniela; Salierno, Francesco Giuseppe; De Cegli, Rossella; Di Malta, Chiara; Svelto, Maria; Lanzara, Carmela; Maddaluno, Marianna; Wanderlingh, Luca Giorgio; et al.
Abstract: Lysosomal degradation of the endoplasmic reticulum (ER) via autophagy (ER‐phagy) is emerging as a critical regulator of cell homeostasis and function. The recent identification of ER‐phagy receptors has shed light on the molecular mechanisms underlining this process. However, the signaling pathways regulating ER‐phagy in response to cellular needs are still largely unknown. We found that the nutrient responsive transcription factors TFEB and TFE3—master regulators of lysosomal biogenesis and autophagy—control ER‐phagy by inducing the expression of the ER‐phagy receptor FAM134B. The TFEB/TFE3‐FAM134B axis promotes ER‐phagy activation upon prolonged starvation. In addition, this pathway is activated in chondrocytes by FGF signaling, a critical regulator of skeletal growth. FGF signaling induces JNK‐dependent proteasomal degradation of the insulin receptor substrate 1 (IRS1), which in turn inhibits the PI3K‐PKB/Akt‐mTORC1 pathway and promotes TFEB/TFE3 nuclear translocation and enhances FAM134B transcription. Notably, FAM134B is required for protein secretion in chondrocytes, and cartilage growth and bone mineralization in medaka fish. This study identifies a new signaling pathway that allows ER‐phagy to respond to both metabolic and developmental cues. Synopsis: The signalling pathways inducing autophagic degradation of the endoplasmic reticulum (ER‐phagy) to regulate cellular homeostasis are ill‐defined. Here, ER‐phagy in chondrocytes promoting bone development is found to be regulated by fibroblast growth factor 18 (FGF18), which induces nuclear translocation of TFEB/TFE3 transcription factors and expression of FAM134B. MiTF/TFE transcription factors promote expression of FAM134B and ER‐phagy in mammalian cells. Prolonged starvation leads to the activation of the TFEB/TFE3‐FAM134B axis and ER‐phagy. In chondrocytes, FGF18 induces ER‐phagy through JNK‐mediated degradation of the IRS1 protein. FAM134B is required for protein secretion in chondrocytes, and for cartilage growth and bone mineralization in medaka fish. Abstract : Nuclear translocation of TFEB/TFE3 transcription factors and expression of FAM134B downstream of FGF18 signalling induce ER‐phagy in chondrocytes to promote bone development.